2023
DOI: 10.37708/psyct.v16i1.701
|View full text |Cite
|
Sign up to set email alerts
|

Health Professions Students' Mental Well-Being and Perceived Health - Тhe Impact of Optimism, Resilience, Religiosity and Stress

Abstract: The study explored the impact of optimism, resilience and religiosity on the mental well-being and perceived health as well as their role in the perceived stress and mental well-being relation in health professions’ students. The study was carried out online with a total of 123 students in medicine, nursing, assistant-pharmacists and social workers. Analyses suggest that optimism and resilience were associated with the stress appraisal as less intensive, less threatening and more controllable. Religiosity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(67 reference statements)
0
0
0
Order By: Relevance
“…In addition, negative emotions are viewed as barriers to AI readiness that require educational efforts to develop students’ resilience to overcome obstacles. Many studies have simultaneously confirmed the positive effects of resilience and optimism on work outcomes (e.g., Miteva, 2023) and found that they were the best predictors of work engagement (Nieto et al, 2022), which provides some support for H16.…”
Section: Literature Review and Hypothesesmentioning
confidence: 87%
“…In addition, negative emotions are viewed as barriers to AI readiness that require educational efforts to develop students’ resilience to overcome obstacles. Many studies have simultaneously confirmed the positive effects of resilience and optimism on work outcomes (e.g., Miteva, 2023) and found that they were the best predictors of work engagement (Nieto et al, 2022), which provides some support for H16.…”
Section: Literature Review and Hypothesesmentioning
confidence: 87%
“…Emotional health is key for healthcare students to experience success, sustain longevity in their course and career, facilitate the environment to provide quality patient care and boost their own wellbeing in preparation for the workforce. 11 Research into podcasting specifically to radiography students is growing in the literature, 12,13 and to the best of our knowledge, there are no published studies that explore the use of podcasts to support wellbeing in radiography students.…”
Section: Podcasts For Studentsmentioning
confidence: 99%